Delineating specific regions of N- terminal domain of T3SS ATPase YsaN of Yersinia enterocolitica governing its different oligomerization states - Kumar, Rajeev; Roy, Chittran; Datta, Saumen (Frontiers in Molecular Biosciences, 2022)
Oligomerization of YsaN, a putative T3SS-ATPase is a necessary and crucial event for T3SS functioning in Yersinia enterocolitica. Different oligomeric states have been proposed for similar ATPases, yet, the true nature of its activation and formation of different oligomers is still poorly understood. In-vitro studies of YsaN reveal that its oligomerization occurs as a result of active catalysis of ATP in an ATP concentration-dependent manner following two-step cooperative kinetics. Also, the N-terminal 83 amino acid residues of YsaN are crucial for higher-order oligomer formation while YsaN∆83 is capable of hexamer formation upon oligomerization. Enzyme kinetics study shows reduced ATPase activity of YsaN∆83 (3.21 ± 1.25 μmol/min/mg) in comparison to YsaN (9.076 ± 0.72 μmol/min/mg). AFM and negative-TEM study of YsaN and YsaN∆83 oligomer suggest that the formation of higher-order oligomer (probably dodecamer) occurs by stacking of two hexamers through their N-terminal faces involving N-terminal 83 amino acid residues which have been further supported by the docking of two hexamers during the in-silico study. Conclusively, distinct regions of the N-terminal domain of YsaN are involved in the formation of the partially active hexamer, and the most active higher-order oligomer.